Novel and Improved Process for the Preparation of Citalopram - Pulla Reddy, M.; Bhujanga Rao, A.K.S.; Usharani, V.; Dubey, P.K. (Asian Journal of Chemistry, 2010)
A novel process for the preparation of citalopram (1) has been described. The key intermediate 1-(4-fluorophenyl)-1,3-dihydroisobenzofuran-5-carbonitrile (2) of citalopram is prepared using novel intermediates. The process involves simple acylation, hydrolysis and reduction, which can be easily adapted to commercial scale.